Трансформація моделі промислової політики задля забезпечення економічного розвитку України - Дука, Анастасія Петрівна; Залєвська-Шишак, Анна Дмитрівна (My University, 2014)
У статті обґрунтовано необхідність переосмислення ролі промислової політики в сучасних умовах розвитку економіки. На основі аналізу трансформаційних процесів у світовому економічному та технологічному просторі розкрито пріоритетну роль промисловості в досягненні цілей економічного розвитку України. Аргументовано, що промисловий сектор вимагає інноваційного оновлення і стимулювання з боку держави. З огляду на це авторами висунуто ідею інноваційної індустріалізації та визначено основні напрями її втілення у практик вітчизняного господарювання. The objective precondition of the change of Ukrainian contemporary industrial policy’s vector is beginning of a new stage of the industrial revolution in economically developed countries. This process is caused by transition to a massive robotic industrial base, that will lead to significant cost reduction in the production sphere; by change in the industrial policy’s ideology in the direction of organizing a new industrial production’s types; by complication of supply chains, that necessitates transportation cost’s reduction aimed to maintaining the necessary amounts of profit; by reorientation of demand of massive good’s consumers towards their manufacturing under the specific order. The purpose of this article is substantiating necessity to change the approaches to formation of the industrial policy oriented to the development and innovative renewal of the industry. Results. Taking into account importance of the industrial sector for the further qualitative changes in national economy, realization of the industrial policy will be effective only on condition of selecting appropriate model.
Keywords: кафедра економіки праці та менеджменту; економічний розвиток; іndustrial policy; globalization; глобалізація